FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA MEMILIH LINTAS MINAT EKONOMI KELAS X MIA DI SMAN 8 PONTIANAK - Junaidi, Junaidi; Ulfah, Maria; Khosmas, F Y (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out how interests and factors that influence the interest of students choose cross-economy class X MIA in Pontianak 8th Public High School. The research method used is a descriptive method with a survey study form. The data source of this study was 12 students consisting of 4 classes, where the students were selected based on the odd semester test scores categorized as high, medium, and under the KKM. Data collection techniques used consisted of: direct observation techniques, direct communication techniques, and documentary study techniques. While the data collection tools used are observation, interviews, and documentation.Based on the results of the results of the research conducted, it shows that students of class X MIA who choose to cross economic interests are in the medium category. Factors that influence interest are divided into 5 aspects that become factors that are formed, namely: 1) Talent factors from 12 students who answer influenced by talent factors 3 students, 2) Factors of ideals of 12 students who responded influenced by the ideals of 5 students, 3) Family factors of 12 students who responded were influenced by family factors of 2 students, 4) Friend factors of 12 students who responded influenced by Friend Factors of 2 students, and 5) School factors of 12 students who answered did not influence them in voting across economic interests.Â Keywords: Factors Affecting Interest, Interest